Are non‐invasive fibrosis markers for chronic hepatitis B reliable in sub‐Saharan Africa?. (23rd March 2017) - Desalegn, Hailemichael; Aberra, Hanna; Berhe, Nega; Gundersen, Svein G.; Johannessen, Asgeir
Abstract: Background: In the absence of liver biopsy, the World Health Organization recommends non‐invasive tests, such as aspartate aminotransferase to platelet ratio index and FIB‐4, to assess liver fibrosis in patients with chronic hepatitis B. However, these tests are not well validated in sub‐Saharan Africa. Recently, a new marker, gamma‐glutamyl transpeptidase to platelet ratio, was found to be more accurate in an African setting, but this needs confirmation in other cohorts. Methods: A treatment program for chronic hepatitis B was initiated in Addis Ababa, Ethiopia, in 2015. Non‐invasive tests were compared with transient elastography (Fibroscan 402, Echosense, France) using the following thresholds: no fibrosis (≤7.9 kPa), significant fibrosis (>7.9 kPa) and cirrhosis (>11.7 kPa). The diagnostic accuracy was estimated by calculating the area under the receiver operating characteristics curve. Results: Of 582 treatment‐naïve patients, 141 (24.2%) had significant fibrosis and 90 (15.5%) had cirrhosis. The area under the receiver operating characteristics curve of aspartate aminotransferase to platelet ratio index, FIB‐4 and gamma‐glutamyl transpeptidase to platelet ratio was high both to diagnose significant fibrosis (0.79 [95% CI 0.75‐0.84], 0.79 [95% CI 0.75‐0.84], 0.80 [95% CI 0.75‐0.85]) and cirrhosis (0.86 [95% CI 0.81‐0.91], 0.86 [95% CI 0.81‐0.91], 0.87 [95% CI 0.82‐0.91]). The specificity was high for all tests (94%‐100%); however, the sensitivity was poor both to detect fibrosis (10%‐45%) and cirrhosis (10%‐36%). Conclusions: Aspartate aminotransferase to platelet ratio index, FIB‐4 and gamma‐glutamyl transpeptidase to platelet ratio had good diagnostic properties to detect liver fibrosis and cirrhosis in patients with chronic hepatitis B in East Africa. However, the sensitivity was low, and only 10% of patients with cirrhosis were detected using aspartate aminotransferase to platelet ratio index at the World Health Organization recommended threshold.